The clip-on method Cady Noland - Noland, Cady 1956-; Anastas, Rhea 1969- (Cady Noland, Rhea Anastas, and Robert Snowden, 2021)
"THE CLIP-ON METHOD contains writing by Cady Noland, sociological essays selected by the artist, and a considerable amount of exhibition photography from the 1980s to the present." - Clip-on method website, gesehen 30.11.2021
Keywords: Noland, Cady -- 1956-; Concept-art; Ausstellungskatalog -- Galerie Buchholz -- 17.06.2021-18.09.2021 -- New York, NY; Bildband